Factors Influencing Drug Abuse Among Adolescents in the Coastal Area of Jember: A Phenomenological Study - Malinda Capri Nurul Satya; Lisus Setyowati; Faiqatul Hikmah; Yoswenita Susindra; M. Nur Khamid (Puslitbang Sinergis Asa Professional, 2026)
Drug abuse among adolescents remains a critical public health concern, especially in coastal areas with socioeconomic challenges and limited parental supervision. This study aimed to explore the predisposing factors influencing adolescents’ behavior against drug abuse, focusing on knowledge, beliefs, and cultural perceptions. This study used predisposing factors as the main variable based on the PRECEDE–PROCEED theory. A qualitative phenomenological approach was conducted involving five junior high school students (Grades VII–IX) from a coastal school in Jember, with inclusion criteria ever used drugs, willingness to participate as respondents, and the ability to communicate effectively. The participants were selected using purposive sampling. Data were collected through in-depth interviews, observations, and document reviews, and analyzed using Interpretative Phenomenological Analysis (IPA). Results showed that adolescents possessed limited and often inaccurate knowledge, mostly obtained from peers. Although they recognized religious prohibitions, moral beliefs were weakly internalized and failed to prevent substance use. Cultural normalization of smoking, alcohol, and drug availability reinforced permissive attitudes. This study concludes that knowledge, beliefs, and cultural perceptions influence drug abuse behavior among coastal adolescents in Jember. Although these adolescents are aware of the dangers of drugs, their limited understanding, weak internalization of religious and moral values, and permissive cultural norms make them more vulnerable. Furthermore, a peer-dominated environment and the easy accessibility of drugs further exacerbate the problem.